Analisa Cross Culture, Organizational Structure dan Corporate Culture Type McDonald’s - Suyanti, Suyanti; Monica, Iveren; Cindy, Cindy; Seputra, Jeremy Kent; Wang, Thalia; Sentoso, Antony (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
McDonald's has had a huge impact on pop culture and fast food around the world. This company continues to adapt to changes in food trends and consumer demands and is committed to providing consistent and quality fast food. Implementing good management integration and good organizational structure must be prioritized by Mc Donald's. Several aspects illustrate Mc Donald's efforts in pursuing this, namely, Training and Education, Waste and Energy Management, Human Resources and Welfare, Commitment to protecting the Environment. The social responsibility aspect is very important for the McDonald's company. This research is aimed at analyzing the work and social culture that occurs at McDonald's, the method used in this research is descriptive data analysis, the conclusion that can be drawn is that McDonald's can ensure that every employee feels valued and has the same opportunity to contribute. This can also create a dynamic and innovative culture.